“There are things I want to say but you do not ask”: a comparison between standardised and individualised evaluations in substance use treatment - Alves, Paula Cristina Gomes (2020)
There has been an increasing call for service users to be more actively involved with the evaluation of treatment outcomes. One strategy to impove such involvement is to ask service users to contribute with their own criteria for evaluation by sharing their personal story and perspective about their clinical situation. In this cross-sectional study, we contrasted the contents elicited by service users completing two individualised measures against the contents of three widely used standardised measures. We also compared two methods to generate individualised data using self-report and interview-based instruments (PSYCHLOPS and PQ). Following a thematic comparison approach, we found that one quarter of the problems reported by patients in individualised measures were not covered by any of our standardised comparators. Also, half of our sample generated at least one problem whose theme was not covered by any of the three standardised measures. We also found that patients in this population have many other concerns beyond drug use. These included psychological (e.g. interpersonal relationships) and socio-economic (e.g. money) problems, which were frequently reported. Our study suggests that listening to service users’ stories allows us to capture issues of importance to service users in substance use treatment, which may be underestimated by standardised measures.